2011
DOI: 10.1016/j.gca.2011.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Short chain ladderanes: Oxic biodegradation products of anammox lipids

Abstract: Anammox, the microbial anaerobic oxidation of ammonium by nitrite to produce dinitrogen gas, has been recognized as a key process in both the marine and freshwater nitrogen cycles, and found to be a major sink for fixed inorganic nitrogen in the oceans. Ladderane lipids are unique anammox bacterial membrane lipids that have been used as biomarkers for anammox bacteria in recent and past environmental settings. However, the fate of ladderane lipids during diagenesis is as of yet unknown. In this study, we perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The GC2 retention position of the C 10 authentic acid methyl ester ( Figure S1) and the tentative identification of the C 9 parent acid ( Figure S7) suggested that some of the C 11 + acids present in the OSPW might have this skeleton. Figure 1B; VII), similar in structure to short-chain ladderane fatty acids previously identified as degradation products of ladderane lipids [36]. Ladderane lipids are specific for bacteria capable of anaerobic ammonium oxidation (anammox) and therefore the acids can be used as biomarkers for anammox bacteria [52].…”
Section: Bicyclic Acidssupporting
confidence: 52%
See 1 more Smart Citation
“…The GC2 retention position of the C 10 authentic acid methyl ester ( Figure S1) and the tentative identification of the C 9 parent acid ( Figure S7) suggested that some of the C 11 + acids present in the OSPW might have this skeleton. Figure 1B; VII), similar in structure to short-chain ladderane fatty acids previously identified as degradation products of ladderane lipids [36]. Ladderane lipids are specific for bacteria capable of anaerobic ammonium oxidation (anammox) and therefore the acids can be used as biomarkers for anammox bacteria [52].…”
Section: Bicyclic Acidssupporting
confidence: 52%
“…These have cyclopropyl-or cyclobutyl rings; the former are present in carane-and thujane-type compounds and the latter present in bicyclo[3. [36]. For the acids with a C 7 core and the requisite substituents, there are four structural types (examples given in Figure 1B; I-III), for the C 8 core acids, six (e.g.…”
Section: Accepted By J Chromatogr Amentioning
confidence: 99%
“…The fatty acid fractions were dissolved in acetone, filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filters (4 mm diameter), and analyzed by high performance liquid chromatography coupled to positive ion atmospheric pressure chemical ionization tandem mass spectrometry (HPLC/APCI-MS/MS) in selective reaction monitoring (SRM) mode following Hopmans et al ( 2006 ) including the recent modifications described by Rush et al ( 2012b ). Ladderane lipids were quantified using external calibration curves of three standards of isolated methylated ladderane fatty acids (C20-[3]-ladderane fatty acid, and C20-[5]-ladderane fatty acid; Hopmans et al, 2006 ; Rush et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, it has so far not been possible to assess anammox further back in time using ladderane lipids as they are not resistant to the degradative stresses of sediment burial. Ladderane fatty acids undergo b-oxidation in the presence of even very low oxygen concentrations to form short chain ladderane fatty acids, which have been found in sediments underlying OMZs (Rush et al, 2011;. However, these too appear to undergo further degradation, and these Arabian Sea sediments are currently the oldest known detection of past anammox activity (Jaeschke et al, 2009).…”
Section: Application Of Biomarkers To Interpret Nitrogen Cycling In Tmentioning
confidence: 99%